Autologous Contralateral and Ipsilateral Rotational Penetrating Keratoplasty – A Case Series and Mini-Review - Quintin, Adrien; Serfözö, Alexandra; Daas, Loay; Suffo, Shady; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2024)
Corneal stromal opacities can severely impact visual acuity if they are located in the visual axis. Homologous penetrating keratoplasty (HPK) is usually the preferred surgical option in such clinical circumstances. However, autologous penetrating keratoplasty (APK) could be an immunologically safer alternative. The purpose of this study was to report the surgical technique, indications, and (dis)advantages of ipsilateral rotational and contralateral APK, as well as pre- and postoperative clinical findings of four patients who underwent contralateral APK. In ipsilateral rotational APK, eccentric trephination places the central corneal opacity at the excision edge, whereafter the corneal button is rotated to clear the visual axis. Contralateral APK is suitable for more specific clinical situations with corneal opacity in a functionally much better eye. Clear cornea of the (almost) blind eye suffering from a noncorneal pathology is transplanted to the potentially better seeing eye suffering from a corneal pathology, followed by HPK in the (almost) blind donor eye. After 18 months, potentially better-seeing eyes improved from logMAR 1.3 to 0.6 in visual acuity, with most HPK-treated weaker eyes matching preoperative levels. Considering ipsilateral rotational and contralateral APK before moving on straight towards HPK is crucial in select cases. Autologous contralateral keratoplasty should be preferred for patients with (1) corneal scars in a potentially better seeing eye and (2) a clear cornea in an (almost) blind eye, especially in cases of high risk for graft rejection.
Keywords: contralateral autologous keratoplasty; ipsilateral rotational autologous keratoplasty; penetrating keratoplasty; central corneal scar